2016
DOI: 10.5539/ijef.v8n5p111
|View full text |Cite
|
Sign up to set email alerts
|

Bank Transparency and Risk Taking: Empirical Evidence from Tunisia

Abstract: An important unresolved issue in finance is the extent to which bank transparency promotes or undermines banking risk-taking. Financial accounting information is an essential component of transparency and a necessary condition for market discipline. This latter can be conceptualized as a market-based incentive scheme with which investors in banking securities penalize banks for greater risk-taking by asking for higher returns on their investments. However, in developing countries, where financial markets are i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Based on the value maximization principle, financial institutions have the tendency to maximize the shareholders' value, without properly measuring their risky behaviors. Many studies have highlighted the lack of transparency and understandability in the activities of financial institutions as the primary cause for the failure to detect such behaviors (Dhouibi et al 2016;Bushman, 2016;Mehran & Mollineaux, 2012;Nier and Baumann, 2006). Such features diminished the function of market discipline in financial institutions.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the value maximization principle, financial institutions have the tendency to maximize the shareholders' value, without properly measuring their risky behaviors. Many studies have highlighted the lack of transparency and understandability in the activities of financial institutions as the primary cause for the failure to detect such behaviors (Dhouibi et al 2016;Bushman, 2016;Mehran & Mollineaux, 2012;Nier and Baumann, 2006). Such features diminished the function of market discipline in financial institutions.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Many studies have suggested a correlation between the excessive risk taking behaviors of financial institutions with the opacity and complexity of their activities (Dhouibi et al 2016;Bushman, 2016;Mehran & Mollineaux, 2012;Nier & Baumann, 2006). The studies listed have highlighted the importance in the role of transparency and understandability towards enhancing market discipline of financial institutions, which will in turn limit their risky behaviors.…”
Section: Role Of Information and Disclosures In Mitigating Excessive mentioning
confidence: 99%